PENERAPAN METODE BERMAIN PERAN DALAM PEMBELAJARAN KETERAMPILAN BERBICARA MATERI DIALOG DRAMA SISWA KELAS VI SD - Sutardi; Anis Rahmawati (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2023)
his study aims to describe the effectiveness of applying the role-playing method in teaching speaking skills through drama dialogues in grade VI of SDN Trenggulunan II Ngasem Bojonegoro. The background of this research is the low confidence and limited ability of students in expressing ideas through dialogues, which requires a creative and contextual learning method that can enhance their speaking courage. This research employed a descriptive qualitative approach with a case study design. The subjects were grade VI students, focusing on student activities, teacher activities, and students’ learning outcomes. Data were collected through observation, documentation, and speaking skill tests, then analyzed descriptively by calculating percentages and comparing test results with the Minimum Mastery Criteria (KKM). The results showed that the application of the role-playing method significantly improved students’ learning activities. Student activity observation gained an average score of 95 in the very good category, where most students actively participated in discussions, confidently delivered dialogues, and expressed roles according to the drama characters. The recap indicated 62 indicators in the good category, 26 in the fair category, and only 4 in the poor category. In addition, the results of speaking skill tests also increased compared to before the method was applied. The role-playing method not only improved students’ speaking skills but also fostered self-confidence, cooperation, imagination, and social skills in line with the principles of the Merdeka Curriculum. It can be concluded that the role-playing method is effective in improving students’ speaking skills in drama dialogues, while also providing enjoyable, interactive, and meaningful learning experiences